Hsp90 Levels in Idiopathic Inflammatory Myopathies and Their Association With Muscle Involvement and Disease Activity: A Cross-Sectional and Longitudinal Study - Štorkánová, Hana; Oreská, Sabína; Špiritović, Maja; Heřmánková, Barbora; Bubová, Kristýna; Kryštůfková, Olga; Mann, Heřman; Komarc, Martin; Slabý, Kryštof; Pavelka, Karel; Šenolt, Ladislav; Zámečník, Josef; et al. (Frontiers in Immunology, 2022)
Background: Heat shock proteins (Hsp) are chaperones playing essential roles in skeletal muscle physiology, adaptation to exercise or stress, and activation of inflammatory cells. We aimed to assess Hsp90 in patients with idiopathic inflammatory myopathies (IIM) and its association with IIM-related features. Methods: Hsp90 plasma levels were analyzed in a cross-sectional cohort (277 IIM patients and 157 healthy controls [HC]) and two longitudinal cohorts to assess the effect of standard-of-care pharmacotherapy (n=39 in early disease and n=23 in established disease). Hsp90 and selected cytokines/chemokines were measured by commercially available ELISA and human Cytokine 27-plex Assay. Results: Hsp90 plasma levels were increased in IIM patients compared to HC (median [IQR]: 20.2 [14.3–40.1] vs 9.8 [7.5–13.8] ng/mL, p<0.0001). Elevated Hsp90 was found in IIM patients with pulmonary, cardiac, oesophageal, and skeletal muscle involvement, with higher disease activity or damage, and with elevated muscle enzymes and crucial cytokines/chemokines involved in the pathogenesis of myositis (p<0.05 for all). Plasma Hsp90 decreased upon pharmacological treatment in both patients with early and established disease. Notably, Hsp90 plasma levels were slightly superior to traditional biomarkers, such as C-reactive protein and creatine kinase, in differentiating IIM from HC, and IIM patients with cardiac involvement and interstitial lung disease from those without these manifestations. Conclusions: Hsp90 is increased systemically in patients with IIM. Plasma Hsp90 could become an attractive soluble biomarker of disease activity and damage and a potential predictor of treatment response in IIM.